To solve the expression 5(7x + 6)(x - 1) - 6, we first need to distribute the 5 into the parentheses, then simplify the expression further.
Let's start by using the distributive property on the expression 5(7x + 6):
5 * 7x = 35x
5 * 6 = 30
So, the expression becomes: 35x + 30(x - 1) - 6
Next, let's distribute the 30 into the parentheses:
30 * x = 30x
30 * -1 = -30
The expression now becomes: 35x + 30x - 30 - 6
Combining the like terms and simplifying further:
(35x + 30x) - (30 + 6) = 65x - 36
Therefore, the simplified expression is 65x - 36.
5(7x + 6) (x - 1) - 6
1 answer